(untitled) (International relations and international law Journal, 2016)
Due to the reform of the legal system laid the foundations of an independent judiciary, the rule of law has consistently provided. Implementation of effective justice judiciary suggests study and practical use of foreign experience of formation and functioning of the judicial system. In this regard, the activities of the German judicial system, the analysis of the legal status of judges in the system of administrative justice of Germany is an urgent task. This article discusses the place of the administrative courts in the German judicial system. The author makes an attempt to analyze the prerequisites for the formation of German judicial system . It is studied the role of various factors influencing the formation of the German court system. During the study, the authors identified administrative and legal status of administrative judges in Germany. During the study, the authors identified administrative and legal status of administrative judges in Germany.